1986
DOI: 10.1016/s0006-3495(86)83556-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction forces between red cells agglutinated by antibody. II. Measurement of hydrodynamic force of breakup

Abstract: The expressions derived in the previous paper for the respective normal, F3, and shear forces, Fshear, acting along and perpendicular to the axis of a doublet of rigid spheres, were used to determine the hydrodynamic forces required to separate two red cell spheres of antigenic type B crosslinked by the corresponding antibody. Cells were sphered and swollen in isotonic buffered glycerol containing 8 X 10(-5) M sodium dodecyl sulfate, fixed in 0.085% glutaraldehyde, and suspended in aqueous glycerol (viscosity:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 27 publications
4
48
0
Order By: Relevance
“…Hence, the fluid forces present in our system range from 35 pN at 0.32 dynes/cm2 to 110 pN at 1.0 dynes/cmz. Since this range of forces is consistent with the estimated strength of a single receptor/ligand bond (<I00 pN; Tha et al, 1986;Evans et al, 1991), it seems possible that adhesion between a B16-FI0 melanoma cell and Lu-ECAM-1 is mediated by a single bond and that this single bond is not strong enough to mediate tumor cell arrest at high shear stresses in vitro.…”
Section: Discussionsupporting
confidence: 65%
“…Hence, the fluid forces present in our system range from 35 pN at 0.32 dynes/cm2 to 110 pN at 1.0 dynes/cmz. Since this range of forces is consistent with the estimated strength of a single receptor/ligand bond (<I00 pN; Tha et al, 1986;Evans et al, 1991), it seems possible that adhesion between a B16-FI0 melanoma cell and Lu-ECAM-1 is mediated by a single bond and that this single bond is not strong enough to mediate tumor cell arrest at high shear stresses in vitro.…”
Section: Discussionsupporting
confidence: 65%
“…These arrests could be ascribed to well defined interactions between endothelial E-selectin and leukocyte ligand since they were inhibited by specific antibodies. In view of previous theoretical [26] and experimental [24,27] work, it was assumed that a single molecular bond could mediate cell arrest. Analysing the statistics of arrest duration, it was concluded that the dissociation rate of an Eselectin mediated bond was about 0.5 s −1 .…”
Section: Detection Of Single Bonds -Lifetime Determinationmentioning
confidence: 99%
“…Accordingly, experiments were carried out using swollen, sphered and glutaraldehyde-fixed red cells of antigenic type B suspended in aqueous glycerol containing 0.15 M NaCI and known amounts of anti B-antibody (61). Doublets of cells formed by two-body collisions at very low shear stresses were observed as they entered the flow tube, and then tracked in the traveling microtube apparatus in a steadily accelerating Poiseuille flow until break-up.…”
Section: Colloidal Suspensionsmentioning
confidence: 99%